There your heart lies [large type] : a novel - Gordon, Mary, 1949- (Thorndike Press, a part of Gale, a Cengage Company, 2017)
Marian cut herself off from her wealthy, conservative Irish Catholic family when she volunteered during the Spanish Civil War--an experience she has always kept to herself. Now in her nineties, she shares her Rhode Island cottage with her granddaughter Amelia, a young woman of good heart but only a vague notion of life's purpose. Their daily existence is intertwined with Marian's secret past: the blow to her youthful idealism when she witnessed the brutalities on both sides of Franco's war and the romance that left her trapped in Spain in perilous circumstances for nearly a decade. When Marian is diagnosed with cancer, she finally speaks about what happened to her during those years--personal and ethical challenges nearly unthinkable to Amelia's millennial generation, as well as the unexpected gifts of true love and true friendship. Marian's story compels Amelia to make her own journey to Spain, to reconcile her grandmother's past with her own uncertain future.